Psychological profile of correctional child (andikpas) of sexual violence in child correctional institution (LPKA) Class II Muara Bulian Jambi: Psychological profile of correctional child of sexual violence in child correctional institution - Rofi'ah, Nisrina; Pramudiani, Dessy; Raudhoh, Siti (Mediapsi, 2024)
Cases of sexual violence against children are increasingly prevalent in Indonesia and involve underage individuals as perpetrators. Criminal profiling can be carried out to find out the background and factors that influence these actions. This research uses qualitative research methods, through a narrative approach, and uses data analysis according to Miles and Huberman's theory. Data validity using the degrees of trust (credibility) test method. The respondents in this study were three adolescent perpetrators of sexual violence against children and were assessed using observation, interviews, document studies, and 6 types of psychological tests. The results of this study show that the three respondents have a psychological profile, namely having a less harmonious relationship with the family, experiencing academic problems, already knowing the victim from before the incident, the scene of the incident being in a quiet location, having a motive to fulfill sexual urges, and making persuasion and threats to the victim. Parents and other adults in the adolescent environment should prioritize the psychological well-being of adolescents to prevent the emergence of sexual violence in adolescents, given that there are both internal and external factors that encourage violent behavior in adolescents.Keywords: criminal profiling, correctional child, sexual violence